Impact of Stock Market Manias and Panics on the U.S. Labor Market - Douglas Mwangi Waithaka; Michael Jan Kendzia (Institute of Labor Economics (IZA), 2024)
History teaches valuable lessons. This article examines the performance of the stock market during various boom and bust phases over the last forty years in the United States. By doing so, four previous manias and panics scenarios are analyzed, including the 1987 black Monday crash, the Dotcom bubble in the early 2000s, the 2008 financial crisis, and the 2019 Covid pandemic. At the same time, the unemployment rate, the growth domestic product (GDP) per capita growth rate, the conference board's leading economic index and the wages growth rate are considered. Econometric models were finally used to study the markets relationships. The study finds that the labor market lags the stock market during manias and panics, supporting the hypothesis of a delayed response in the labor market. The unemployment rate reacted particularly late to the black Monday crash, the Dotcom bubble and the 2008 financial crisis. The leading economic index followed the stock market closest and with the slightest lag. Wages growth rate and the growth domestic product per capita growth rate reacted with varying degrees to each mania and panic episodes.
Keywords: B23; B27; E24; G15; 330; S&P 500; leading economic index; wage growth rate; unemployment rate